K(+) Channel Modulatory Subunits KChIP and DPP Participate in Kv4-Mediated Mechanical Pain Control - Kuo, Yen-Ling (J Neurosci, 2017)
The K(+) channel pore-forming subunit Kv4.3 is expressed in a subset of nonpeptidergic nociceptors within the dorsal root ganglion (DRG), and knockdown of Kv4.3 selectively induces mechanical hypersensitivity, a major symptom of neuropathic pain. K(+) channel modulatory subunits KChIP1, KChIP2, and DPP10 are coexpressed in Kv4.3(+) DRG neurons, but whether they participate in Kv4.3-mediated pain control is unknown. Here, we show the existence of a Kv4.3/KChIP1/KChIP2/DPP10 complex (abbreviated as the Kv4 complex) in the endoplasmic reticulum and cell surface of DRG neurons. After intrathecal injection of a gene-specific antisense oligodeoxynucleotide to knock down the expression of each component in the Kv4 complex, mechanical hypersensitivity develops in the hindlimbs of rats in parallel with a reduction in all components in the lumbar DRGs. Electrophysiological data further indicate that the excitability of nonpeptidergic nociceptors is enhanced. The expression of all Kv4 complex components in DRG neurons is downregulated following spinal nerve ligation (SNL). To rescue Kv4 complex downregulation, cDNA constructs encoding Kv4.3, KChIP1, and DPP10 were transfected into the injured DRGs (defined as DRGs with injured spinal nerves) of living SNL rats. SNL-evoked mechanical hypersensitivity was attenuated, accompanied by a partial recovery of Kv4.3, KChIP1, and DPP10 surface levels in the injured DRGs. By showing an interdependent regulation among components in the Kv4 complex, this study demonstrates that K(+) channel modulatory subunits KChIP1, KChIP2, and DPP10 participate in Kv4.3-mediated mechanical pain control. Thus, these modulatory subunits could be potential drug targets for neuropathic pain. SIGNIFICANCE STATEMENT Neuropathic pain, a type of moderate to severe chronic pain resulting from nerve injury or disorder, affects 6.9%–10% of the global population. However, less than half of patients report satisfactory pain relief from current treatments. K(+) channels, which act to reduce nociceptor activity, have been suggested to be novel drug targets for neuropathic pain. This study is the first to show that K(+) channel modulatory subunits KChIP1, KChIP2, and DPP10 are potential drug targets for neuropathic pain because they form a channel complex with the K(+) channel pore-forming subunit Kv4.3 in a subset of nociceptors to selectively inhibit mechanical hypersensitivity, a major symptom of neuropathic pain.